A critical review of cosmetic treatment outcomes in body dysmorphic disorder. (December 2016) - Bowyer, Laura; Krebs, Georgina; Mataix-Cols, David; Veale, David; Monzani, Benedetta
Highlights: A high proportion of individuals with BDD undergo cosmetic treatments. Few studies have examined cosmetic treatment outcomes in BDD. Cosmetic treatments rarely improve BDD symptoms. There is a need for collaboration across mental health and cosmetic teams. Abstract: A high proportion of individuals with body dysmorphic disorder (BDD) undergo cosmetic treatments in an attempt to 'fix' perceived defect/s in their physical appearance. Despite the frequency with which such procedures are sought, few studies have prospectively examined the outcomes of cosmetic procedures in individuals with BDD. This article aims to critically review the literature and discuss the current debate that exists on outcomes of cosmetic treatment for individuals with BDD. An emerging literature suggests the majority of individuals with BDD have poor outcomes after cosmetic interventions; however, based on the current literature, it cannot be fully ruled out that certain individuals with mild BDD and localised appearance concerns may benefit from these interventions. Gaps in the current literature are highlighted, alongside recommendations for future research. Carefully conducted longitudinal studies with well-characterised patient populations are needed.